REALITY OF PROTECTION FOR SEXUAL VIOLENCE VICTIMS: COMPREHENSIVE PROTECTION ANALYSIS FOR SEXUAL VIOLENCE VICTIMS - Ramada, Diandra Preludio (INDONESIAN JOURNAL OF CRIMINAL LAW STUDIES, 2017)
Lack of research on victims, especially victims of sexual crimes, whereas cases of sexual crimes are increasingly prevalent in the community. Victim protection is urgently needed to address the increasing number of victims who are not immediately noticed as law enforcers pay more attention to the perpetrators, while victims who suffer physically and psychologically, materially and spiritually, are largely ignored. There are two things that make the offer of protection become important for the victim. First, how to make victims for whom the protection is held, they feel that they are given a sense of security and comfort as citizens protected from the evil that constantly lurks. Second, how to ensure that protection institutions can be achieved with adequate social, economic and cultural aspects.This research aims to find two important things: (1). Finding framework and system of victim protection innovation in Semarang (2). Find and understand the most urgent needs of victims for psychological and physical recovery so that victims can reactivate like other citizens. The benefit of this research is to provide scientific information about the opportunities and barriers to the application of innovative protection for victims in the environment. Thus, the institution can be built especially for victims of sexual violence, as well as the preparation of aspirative and compatible programsThe research method used is qualitative research that rely on information from the first hand, both concerning the application of innovation protection and efforts to find the framework of innovation, it will be pursued stages of research stages, ranging from the determination of the object and place of research, the determination of unit analysis and observation unit, to intensive research in the field. Preliminary information was collected through a survey with questionnaires and interview guides. In addition, focus groups will be set up based on the diversity of informants. The deepening of the data is done by combining in-depth interviews and focused discussions.The findings of this research will result in a model of protection that has legitimacy for the community. The protection model is in great demand and beneficial to victims who have not been noticed.